Facing Pro-poor Design of Subsidies for Drinking Water and Sanitation Services in Africa - Caspary, Georg (OECD Publishing, 2007)
Limited capacity to pay, large infrastructure needs and a huge backlog in the construction of sanitation facilities make recourse to cross-subsidies and government-funded subsidies a necessity in Africa. * This Policy Insights introduces the African Economic Outlook 2007
Keywords: Development